2018
DOI: 10.4236/ojapps.2018.85013
|View full text |Cite
|
Sign up to set email alerts
|

Flow of a Second-Grade Fluid between Eccentric Rotating Porous Disks in the Presence of a Magnetic Field

Abstract: This paper is concerned with the steady flow of a second-grade fluid between two porous disks rotating eccentrically under the effect of a magnetic field. A perturbation solution for the velocity field is presented under the assumption that the second-grade fluid parameter β is small. It is also studied the effect of all the parameters on the horizontal force per unit area exerted by the fluid on the disks. It is found that the xand y-components of the force increase and decrease, respectively, when the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…If there is a large gap between both disks, the flow has a separating boundary layer, and this case was studied by Batchelor [2]. Other studies investigated the flow around the eccentric rotating porous disks [3] or the nonli-near vortex structures in obliquely rotating fluid [4].…”
Section: Introductionmentioning
confidence: 99%
“…If there is a large gap between both disks, the flow has a separating boundary layer, and this case was studied by Batchelor [2]. Other studies investigated the flow around the eccentric rotating porous disks [3] or the nonli-near vortex structures in obliquely rotating fluid [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sohail et al [49] reported the heat and mass transfer flow of couple stress fluid past a nonlinear stretching surface for variable properties of magnetic field, thermal conductivity and diffusion coefficient by deriving conducting mass and chemical reaction through Fick's second law. Ersoy [50] focused on the steady flow of a second-grade fluid between two porous eccentrically rotating disks in the presence of magnetic field. He adopted the perturbation solution for the flow under the assumption of small second-grade fluid parameter and revealed that the rising values of Reynolds number provide a surge in the horizontal force.…”
Section: Introductionmentioning
confidence: 99%